Defining indicators for drug overdose emergency department visits and hospitalisations in ICD-10-CM coded discharge data. Issue Volume 27:Issue Suppl 1(2021) (9th April 2021) - Vivolo-Kantor, Alana; Pasalic, Emilia; Liu, Stephen; Martinez, Pedro D; Gladden, Robert Matthew
Abstract : Introduction: The drug overdose epidemic has worsened over the past decade; however, efforts have been made to better understand and track nonfatal overdoses using various data sources including emergency department and hospital admission data from billing and discharge files. Methods and findings: The Centers for Disease Control and Prevention (CDC) has developed surveillance case definition guidance using standardised discharge diagnosis codes for public health practitioners and epidemiologists using lessons learnt from CDC's funded recipients and the Council for State and Territorial Epidemiologists (CSTE) International Classification of Diseases, 10th Revision, Clinical Modification (ICD-10-CM) Drug Poisoning Indicators Workgroup and General Injury ICD-10-CM Workgroup. CDC's guidance was informed by health departments and CSTE's workgroups and included several key aspects for assessing drug overdose in emergency department and hospitalisation discharge data. These include: (1) searching all diagnosis fields to identify drug overdose cases; (2) estimating drug overdose incidence using visits for initial encounter but excluding subsequent encounters and sequelae; (3) excluding underdosing and adverse effects from drug overdose incidence indicators; and (4) using codes T36–T50 for overdose surveillance. CDC's guidance also suggests analysing intent separately for ICD-10-CM coding. Conclusions: CDC's guidance provides health departments a key tool to better monitor drug overdoses in their community. The implementation and validation of this standardised guidance across all CDC-funded health departments will be key to ensuring consistent and accurate reporting across all entities.